Physicochemical Properties of Ambarella Fruit Leather with Variations in Gum Arab Concentration - Safinta Nurindra Rahmadhia; Ratna Sintiya Dewi; Soraya Kusuma Putri (PERTETA, 2025)
Fruit leather is a thin sheet product made from dried fruit pulp until it has a flexible texture and can be rolled. Ambarella was chosen as the raw material because it has a sour taste and is naturally rich in vitamin C. The elasticity of fruit leather is influenced by the type of binding agent used, one of which is gum arab. Gum arab is a polysaccharide from the sap of Acacia sp. that is stable at pH 2–7 and resistant to acidic conditions and high temperatures. This study aimed to determine the changes in physicochemical characteristics of ambarella fruit leather with the addition of gum arab at different concentrations. The formulation used five gum arab concentrations (0%, 0.6%, 0.8%, 1%, and 1.2%) and three replications. The process included preparing puree, mixing with sugar and gum arab, and drying into sheets. Parameters tested were moisture content, pH, total sugar, total soluble solids, vitamin C, crude fiber, thickness, and texture. The results showed chemical properties which are moisture content 14.10–17.08%; pH 3.09–3.47; sugar 20.00–20.02%; soluble solids 72.43–74.77%; vitamin C 5.57–12.61%; and crude fiber 1.58–2.23%. Physical properties such as thickness 1.27–1.31 mm; tensile strength 0.03–0.16 MPa; elongation 7.01–10.53%; hardness 13.66–78.85 N; gumminess 5.28–57.88 N; and chewiness 3.75–49.20 N. It can be said that the variations in gum arab significantly affected both chemical and physical properties of ambarella fruit leather is a healthy snack. Keywords: ambarella, fruit leather, gum arab, vitamin C.